Culture and sporulation of Paenibacillus larvae larvae (White) in not specific culture media - FYLAKTOU (Α. ΦΥΛΑΚΤΟΥ), A.; LIAKOS (Β. ΛΙΑΚΟΣ), B.; ILIADIS (Ν. ΗΛΙΑΔΗΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this experimental study the culture possibility and the sporulation ability of Paenibacillus larvae larvae (White), in simple and compound not specific culture media, in aerobic and anaerobic conditions and in an atmosphere of 5-10% C02 in air, were investigated. The results indicated that P.l.larvae could be cultured in normal culture media, in aerobic or anaerobic conditions. However its growth is significantly delayed and only after 48-72 h incubation, its demonstration becomes evident. In specific culture media like blood agar and Brucella agar and atmosphere of 5-10% C02 in air, it can be developed faster, sporulated more and demonstrated easier. Development and sporulation of P.l.larvae was better in Brucella agar than in blood agar.